Réponses

2013-06-20T18:58:55+02:00

{ a   =    x +   y +   z

{ b   =  2x +  2y +  z

{ c   =  4x +   y + 3z

 

 

{ x   =   a - y - z

{ b   =   2(a - y - z) + 2y + z   =   2a - z

{ c   =   4(a - y - z) + y + 3z   =   4a - 3y - z

 

 

{ x   =   a - y - (2a - b)   =   -a + b - y

{ z   =   2a - b

{ c   =   4a - 3y - (2a - b)   =   2a + b - 3y

 


{ 3x   =   -3a + 3b - 3y

{ z   =   2a - b

{ 3y   =   2a + b - c

 

 

{ 3x   =   -3a + 3b - 3(2a + b - c)   =   -9a + 3c

{ z   =   2a - b

{ 3y   =   2a + b - c

 

 

{ x   =   -3a + c

{ z   =   2a - b

{ y   =   (2a + b - c)/3